Tecnologias no ensino de crianças com paralisia cerebral - OLIVEIRA, Ana Irene Alves de (Brasil, 2017)
Cerebral palsy is a chronic condition characterized by a predominantly sensory-motor dysfunction involving disturbance in muscle tone, posture and voluntary movement. The aim of this study was to investigate the effect of computerized procedures for teaching conditional relationships with pictures and words printed on generalized recombinational reading with four children. All steps were developed using assistive technology (AT), with the Desenvolve ® software for teaching basic prerequisites. Then, training and reading tests with technology derived from the paradigm of stimulus equivalence were carried out. The results provided evidence that the teaching procedure used promoted generalized recombinational reading of new words. The procedures used suggest that the systematic manipulation of the smaller units than words may be a promising strategy for developing reading recombination, combining the paradigm of equivalence with exercises and AT resources in order to contribute and promote inclusive education of students with CP, expanding their social interactions and downplaying their academic difficulties.